Metastatic Carcinoma of the Breast Presenting as Gingival Swelling in the Maxilla: A Case Report - Arun Sadasivan; K. Rakul Nambiar; Deepu George Mathew; Elizabeth Koshi; Roshni Ramesh; Ashna Mariya Benny (Hindawi Limited, 2022)
Background. Metastatic cancers in the oral cavity are usually very rare and are usually an indication of widespread malignancy. In some cases, oral metastasis was found to be the first presentation of distant site tumours. Even though oral metastatic lesions may be found anywhere in the oral cavity, they commonly present in the posterior areas of the jaw bones. Among the soft tissues, the gingiva is the most common site. The presence of inflammation in the gingiva and the role of periodontal microbiota are suggested to play a role in the attraction of metastatic cells. The purpose of this case report is to present a rare case of metastatic breast carcinoma presenting as a gingival enlargement in the maxillary anterior region. Case Presentation. A 37-year-old female patient who underwent modified radical mastectomy for invasive ductal breast carcinoma reported to the dental clinic with a gingival enlargement in the anterior maxillary region. Clinical and radiographic examination showed a rapidly enlarging gingival lesion with destruction of the underlying bone. A wide excision of the entire lesion was done. Histopathological and immunohistochemical (IHC) evaluations were suggestive of infiltrating poorly differentiated adenocarcinoma. Conclusion. This case report presents a metastatic oral lesion in the maxillary anterior region of the primary breast cancer site. The young age of patient and an uncommon site of metastatic lesion are the striking features of this case. We would like to highlight the importance of a thorough clinical, radiological, and histological evaluation of any gingival swelling as it could be a metastatic lesion. IHC staining helps in the diagnosis of the primary site of metastatic carcinomas. An early diagnosis and intervention could reduce the morbidity of the lesion and improve the survival rate.